An Analysis of Letter Recognition Skills Through the Letter Card Box Game in Children Aged 4–5 Years - Desti Rahayu, Yayuk; Andri Nugroho, Aryo; Ngatmini, Ngatmini (Jayapangus Press, 2025)
This study aims to analyze the effectiveness of the letter card box game as an educational medium in enhancing the letter recognition skills of children aged 4–5 years at TK Mutiara Basmallah 1 Tembalang. The research employed a descriptive qualitative approach, with data gathered through observation, interviews, and documentation. The results reveal that the use of the letter card box game significantly improves children's abilities in identifying letter shapes, names, and phonetic sounds. The media successfully captures children’s attention and fosters a joyful, engaging, and interactive learning atmosphere. By incorporating visual, auditory, and kinesthetic learning styles, this media helps strengthen children's cognitive engagement and retention in the learning process. Furthermore, it promotes active participation and collaboration among peers during activities. However, the study also identifies several challenges, including the limited availability of the media, restricted instructional time, and difficulties encountered by some children in distinguishing visually similar letters. These obstacles can be mitigated through the application of more diverse instructional strategies and continuous collaboration among teachers, parents, and the school. Overall, the letter card box game proves to be an effective medium for developing early literacy in young children. It is therefore recommended that schools adopt this media in their curriculum and support it through teacher training programs and enhanced educational resources.